THE SIGNIFICANCE OF CLINICAL-LABORATORY AND MOLECULAR-GENETIC MARKERS IN THE DIAGNOSIS OF NON-ALCOHOLIC FATTY LIVER DISEASE (Novateur Publications, 2025)
Today, non-alcoholic fatty liver disease (NAFLD) is one of the urgent problems of medicine in the field of hepatology. Indeed, In modern hepatology, NASH is the most common diffuse liver disease after the age of 40. The urgency of NASH, progressive growth, and widespread prevalence (20-45%), It is observed among the working-age population, is characterized by the ineffectiveness of specific treatment due to the non-specificity of clinical signs in the initial stage, and the appearance of pronounced clinical signs in the late stages of the disease.